Automotive innovation : the science and engineering behind cutting-edge automotive technology - Hossay, Patrick, 1964- (Boca Raton, FL : CRC Press, 2020)
Automotive Innovation: The Science and Engineering behind Cutting-Edge Automotive Technology provides a survey of innovative automotive technologies in the auto industry. Automobiles are rapidly changing, and this text explores these trends. IC engines, transmissions, and chassis are being improved, and there are advances in digital control, manufacturing, and materials. New vehicles demonstrate improved performance, safety and efficiency factors; electric vehicles represent a green energy alternative, while sensor technologies and computer processors redefine the nature of driving. The text explores these changes, the engineering and science behind them, and directions for the future.
OCLC-licensed vendor bibliographic record.
Keywords: Automobiles -- Technological innovations -- Popular works; Automobiles -- Design and construction -- Popular works; TECHNOLOGY / Electronics / General; TECHNOLOGY / Engineering / Civil; TECHNOLOGY / Engineering / Mechanical